El desarrollo socioeconómico en Latinoamérica: Un análisis a la luz de los objetivos de desarrollo sostenible de las Naciones Unidas - Nieves Carmona González; Carmen Díaz Roldán (Atlantic Review of Economics (ARoEc), 2018)
– Throughout history, when looking at the evolution of the social and economic environment, the sustainability of certain economic policy measures has been questioned; policies that are more criticized even in times of crisis. In response, the sustainable development goals of the United Nations (United Nations, 2015) involve both the revision of traditional development models and also a different strategy regarding the implementation of economic policies. The purpose of this paper is to explore to what extent the economic policies of the countries of Latin America and the Caribbean have been oriented to promote sustainable development. This analysis will allow to have a framework of reference, which will let know to what extent a sustainable economic policy is possible in these countries
Keywords: O20; Q01; 330; Sustainable development; United Nations; Latin America and the Caribbean